Antioxidant potential and identification of active compounds on Kabau seed (Archidendron bubalinum) flesh and husk extract - Fri Rahmawati; Linggom Kurniaty; Maria Bintang (Jurnal Kimia Sains dan Aplikasi, 2020)
Kabau (Archidendron bubalinum) is one of the plants that is often used as food ingredients and has the potential to be developed in the health sector. This study aims to determine the antioxidant potential of kabau seeds using 2,2-diphenyl-1-picril hidrazil (DPPH) and ferric reducing ability power (FRAP) methods and to identify active compounds of kabau seeds using GC-MS. Kabau seeds were macerated using 70% ethanol and 99.9% ethanol. The results showed that 99.9% ethanol extract of kabau seed coat had the highest antioxidant activity with IC50 values of 26.75 ppm for the DPPH method and 121.55 ppm for the FRAP method, respectively. Identification of active compounds using GC-MS showed that 99.9% ethanol extract of kabau seed coat contained the most 9,12-octadecadienoic acid compounds (linoleic acid) so that it could be developed as an antioxidant.